Edwardsiella piscicida: a significant bacterial pathogen of cultured fish - Buján, N; Toranzo, Alicia E; Magariños, B (Diseases of aquatic organisms, 2018)
Edwardsiella piscicida, a Gram-negative, facultative aerobic pathogen belonging to the Enterobacteriaceae family, is the etiological agent of edwardsiellosis in fish and a significant problem in global aquaculture. E. piscicida has been reported from a broad geographical range and has been isolated from more than 20 fish host species to date, but this is likely to be an underestimation, because misidentification of E. piscicida as other species within the genus remains to be resolved. Common clinical signs associated with edwardsiellosis include, but are not limited to, exophthalmia, haemorrhages of the skin and in several internal organs, mild to moderate dermal ulcerations, abdominal distension, discoloration in the fish surface, and erratic swimming. Many antibiotics are currently effective against E. piscicida, although legal restrictions and the cost of medicated feeds have encouraged significant research investment in vaccination for the management of edwardsiellosis in commercial aquaculture. Here we summarise the current understanding of E. piscicida and highlight the difficulties with species assignment and the need for further research on epidemiology and strain variability.